Associations between household characteristics and environmentally persistent free radicals in house dust from two Australian locations - Lee, Wen Ray; Dangal, Prakash; Langan, Gaurav; Lazarevic, Nina; Xu, Zhiwei; Cormier, Stephania A.; Lomnicki, Slawo; Sly, Peter D.; Vilcins, Dwan (Frontiers in Public Health, 2025)
IntroductionThe association between air pollution and adverse health outcomes has been extensively documented, with oxidative stress widely considered a contributing factor. However, the precise underlying mechanism(s) remains unclear. Recent studies suggest that environmentally persistent free radicals (EPFRs) may provide the missing connection between air pollution and its detrimental health effects. Nevertheless, the indoor environment has received limited attention in EPFR research. Therefore, in this study, we measured EPFRs in house dust samples from two locations in Australia and examined household characteristics associated with their presence.MethodsHousehold characteristics and behaviours that influence indoor air quality were collected from an online questionnaire; 24-h indoor and outdoor air quality were measured with a TSI DustTrak™ DRX Aerosol monitor 8,533; annual indoor and outdoor air quality were matched to two validated, satellite-based land-use regression models; and dust samples were collected from house vacuums. Dust samples were analyzed using nano electron paramagnetic resonance (EPR) to determine spin concentrations, g-factor, and delta H peak-to-peak (Hp-p). Key variables were identified using Lasso-penalized regression models, followed by unpenalized linear regression and post-selection inference to estimate coefficients and assess the robustness of the findings.ResultsOur analysis revealed that factors such as extractor fan usage during cooking, exposure to traffic-related air pollution and ambient PM2.5 levels, indoor combustion activities, seasonal variation, housing construction type, ventilation, and cleaning practices were significantly associated with EPFR concentrations in Australian homes. Notably, consistent use of extractor fans during cooking was strongly and consistently associated with lower EPFR concentrations in house dust across both study locations.DiscussionOur research provided insight into the potential impact of household characteristics on EPFR concentrations, which can potentially lead to adverse health effects. Future research should link our research findings on factors affecting indoor EPFRs to their potential health effects.